Assessing the effects of seasonal grazing on holm oak regeneration: Implications for the conservation of Mediterranean dehesas - Carmona, Carlos P.; Azcárate, Francisco M.; Oteros-Rozas, Elisa; González, José A.; Peco, Begoña (Biological Conservation, 2013)
Scattered trees in agricultural landscapes are globally declining due to the intensification of agricultural practices. Dehesas, highly species-diverse Mediterranean open woodlands, are seriously affected by this decline, because of a generalized regeneration failure of oak, which compromise their long-term stability. Traditionally, dehesas were the wintering areas for transhumant herds, but transhumance is disappearing in the Mediterranean, due to multiple causes. Reductions in grazing intensity or grazing abandonment have been proposed to improve oak regeneration in dehesas, but the effect of the recovery of non-continuous grazing practices such as transhumance has not been tested to date. We measured different indicators of holm oak regeneration and condition in dehesas under transhumant grazing and in dehesas under permanent grazing in southern Spain. Oak juveniles were remarkably less browsed and their canopies covered a much higher area in transhumant estates. As a consequence, the median density of saplings was more than four times higher in transhumant than in permanently-grazed estates. Although transhumant grazing is necessarily associated with a reduction in the stocking rate across the year, the timing of grazing was always included as a predictor in the best models to explain the condition and density of holm oak. Our results suggest that the lack of oak regeneration in dehesas can be caused not only by the increases in stocking rates, but also by the recent abandonment of traditional grazing practices like transhumance. We propose the recovery of seasonal grazing regimes based on transhumant pastoralism as a measure to improve the conservation status of dehesas.
Keywords: Agricultural intensification; Agroforestry; Browsing; Quercus ilex; Transhumance